Kampung Dreamworld : a critical look at contemporary nostalgia - Leow, Si Min (2017)
Our modern struggle with accelerated time and rapid progress prompted a global wave of nostalgia. As a response to the fear and uncertainty of the future, nostalgia has been adopted as an individual instrument of survival and a countercultural practice. Contemporary nostalgia serves as a defense mechanism against time, providing us with comfort and allowing us to critically reflect about the present and future. However, our nostalgic tendency to romanticise the past is problematic as it neglects historical facts and realities. Conceived as a theme park, Kampung Dreamworld questions contemporary nostalgia in the context of Singapore and re-examines its purpose in today's constantly shifting world. By bringing to light forgotten histories in a satirical manner, Kampung Dreamworld serves as a form of escapist entertainment with a very real-world sting at its core.